The role of MMP-2 and MMP-9 as prognostic markers in the early stages of tongue squamous cell carcinoma - Aparna, Manikkath; Rao, Lakshmi; Kunhikatta, Vijayanarayana; Radhakrishnan, Raghu (Journal of oral pathology & medicine, 2015)
Background Tongue cancer is the most common intra‐oral malignancy with a high rate of morbidity and mortality owing to its increased propensity for tumor invasion and metastasis. These processes require a controlled degradation of the extracellular matrix. Matrix Metalloproteinase‐2 (MMP‐2) and Matrix Metalloproteinase‐9 (MMP‐9) are known to be important regulators of matrix lysis and play a significant role in the metastasis of malignancies. Aim and objectives To study the expression of MMP‐2 and MMP‐9 in the early stages of tongue squamous cell carcinoma and find the association between their expression and local recurrence, metastasis, and survival rates of the subjects. Materials and methods Fifty‐nine tumor biopsy samples of tongue squamous cell carcinoma in T1N0M0 and T2N0M0 stages were immunostained with MMP‐2 and MMP‐9 antibodies. The immunohistochemical expression was compared with the patient characteristics and outcome. Results Cytoplasmic expression of MMP‐2 correlated with that of MMP‐9 (r = 0.716, P < 0.001). Greater expression of MMP‐2 and MMP‐9 was observed in patients who subsequently developed local recurrence (P = 0.044 and P < 0.001, respectively), regional and/or distant metastasis (P < 0.001 and P = 0.001, respectively) of the tumor. Further, a higher expression of these biomarkers was associated with shorter survival. MMP‐9 was found to have better specificity for local recurrence, metastasis and survival. Conclusion Our results showed that these biomarkers may serve as indicators of a patient's risk potential for poor prognosis and presage the need for more aggressive treatment measures.